The Attributes of Biophilic Design (Educational Buildings Case Study) - Siham, Hiyam (Al-Nahrain Journal for Engineering Sciences, 2023)
Three decades of empirical research have proven that well-being in humans is stimulated by designs that link people to natural elements and landscapes. Environmental psychology research also revealed that these characteristics can lower stress and anxiety while having a positive impact on human productivity. therefore, there were more recent interest from theorists and architects to discover approaches to re-connect the constructed environment with the natural components. One of the most current theories of re-communication and its use in architecture is called "biophilia.". Therefore, the research problem is the lack of knowledge of biophilic architecture and what are the most prominent features affecting the user.  the research aims to shed light on the basics of this design theory as well as testing its design patters in the educational environment to find out which attributes are most effective for users in improving productivity and well-being By adopting the quantitative descriptive approach and based on a questionnaire for the purpose of adopting it in design and to aid in the practical application of the Biophilia idea by designers and architects. The research concluded that there are design features that are more important than others for educational buildings, such as (day light, water, air, plants, landscapes, mobility, integrating the parts to create the whole).